Proceedings of the 1st International Workshop on Earable Computing 2019
DOI: 10.1145/3345615.3361131
|View full text |Cite
|
Sign up to set email alerts
|

Head Motion Tracking Through in-Ear Wearables

Abstract: Head tracking is a fundamental component in visual attention detection, which, in turn, can improve the state of the art of hearing aid devices. A multitude of wearable devices for the ear (so called earables) exist. Current devices lack a magnetometer which, as we will show, represents a big challenge when one tries to use them for accurate head tracking.In this work we evaluate the performance of eSense, a representative earable device, to track head rotations. By leveraging two different streams (one per ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…However, their study has shown that great variability exists in how people wear the sensor in the ear (i.e., different angle/orientations), which further complicates estimating head pose between different subjects. While it is also possible to estimate head orientation using only wireless wearable sensors (e.g., smart ear pieces and head bands) [18,23], these technology are still in nascent stages and are not able to estimate orientations accurately. A recent technology based on near-infrared sensing utilizes pairwise light sensing to infer the incident angle and distance between two sensors [41].…”
Section: Wearable Sensor Based Orientation Measurement and Estimationmentioning
confidence: 99%
“…However, their study has shown that great variability exists in how people wear the sensor in the ear (i.e., different angle/orientations), which further complicates estimating head pose between different subjects. While it is also possible to estimate head orientation using only wireless wearable sensors (e.g., smart ear pieces and head bands) [18,23], these technology are still in nascent stages and are not able to estimate orientations accurately. A recent technology based on near-infrared sensing utilizes pairwise light sensing to infer the incident angle and distance between two sensors [41].…”
Section: Wearable Sensor Based Orientation Measurement and Estimationmentioning
confidence: 99%
“…We can see that the signals for the same activity show similar patterns under both cases, indicating head movements have negligible impact on the sensing signals. 4 In addition, as shown in Figure 5, background noise has no impact on the sensing signals as it is naturally suppressed with the occlusion of human ear. Moreover, as the target motion signals are in frequencies below 50 Hz, any audible background noise can be easily removed with a low-pass filter.…”
Section: Initial Explorationmentioning
confidence: 99%
“…Activity modeling: We can recognise upper body movements, such as head and neck activities [6,21], facial activities and expression [18], and whole-body movements, i.e., walking, standing, falling, etc. [21].…”
Section: Earable As Memory Aidmentioning
confidence: 99%